The gut homeostasis-immune system axis: novel insights into rheumatoid arthritis pathogenesis and treatment - Qi, Peng; Chen, Xin; Tian, Jiexiang; Zhong, Kexin; Qi, Zhonghua; Li, Menghan; Xie, Xingwen (Frontiers in Immunology, 2024)
Rheumatoid arthritis is a widely prevalent autoimmune bone disease that imposes a significant burden on global healthcare systems due to its increasing incidence. In recent years, attention has focused on the interaction between gut homeostasis and the immune system, particularly in relation to bone health. Dysbiosis, which refers to an imbalance in the composition and function of the gut microbiota, has been shown to drive immune dysregulation through mechanisms such as the release of pro-inflammatory metabolites, increased gut permeability, and impaired regulatory T cell function. These factors collectively contribute to immune system imbalance, promoting the onset and progression of Rheumatoid arthritis. Dysbiosis induces both local and systemic inflammatory responses, activating key pro-inflammatory cytokines such as tumor necrosis factor-alpha, Interleukin-6, and Interleukin-17, which exacerbate joint inflammation and damage. Investigating the complex interactions between gut homeostasis and immune regulation in the context of Rheumatoid arthritis pathogenesis holds promise for identifying new therapeutic targets, revealing novel mechanisms of disease progression, and offering innovative strategies for clinical treatment.